2017
DOI: 10.3390/fermentation3040068
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Growth and Ammonia Production of Ruminal Hyper Ammonia-Producing Bacteria by Chinook or Galena Hops after Long-Term Storage

Abstract: Surplus hops (Humulus lupulus L.) that are not needed by the brewing industry could be used as a feed supplement for cattle and other ruminants. Previous research indicates that antimicrobial hops plant secondary metabolites (i.e., α-and β-acids) inhibit methane and ammonia production and promote the growth of ruminant animals. The goal was to determine that hop pellets produced for brewing still possessed the requisite antimicrobial activity after 5-year storage. HPLC (high performance liquid chromatography) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Some results have shown that spent brewers' yeast inhibited rumen ammonia and methane production [25] [26]. Another DOI: 10.4236/aim.2019.912063 990 Advances in Microbiology study indicates that older stored hops are adequately antimicrobial for feeding applications even after they are no longer desirable by brewers [27]. The antimicrobial spectrum of activity of hop phytochemicals should be considered when planning diets to test these co-products.…”
Section: Discussionmentioning
confidence: 99%
“…Some results have shown that spent brewers' yeast inhibited rumen ammonia and methane production [25] [26]. Another DOI: 10.4236/aim.2019.912063 990 Advances in Microbiology study indicates that older stored hops are adequately antimicrobial for feeding applications even after they are no longer desirable by brewers [27]. The antimicrobial spectrum of activity of hop phytochemicals should be considered when planning diets to test these co-products.…”
Section: Discussionmentioning
confidence: 99%
“…Hop acids are known inhibitors of bovine hyper ammoniaproducing bacteria (Flythe, 2009;Flythe et al, 2017a). Supporting the role of hop acids in suppressing ammonia formation by rumen microbes, craft yeast was previously found to generate less ammonia than baker's yeast even in the presence of exogenous amino acids by inhibition of hyper ammonia-producing bacteria (Harlow et al, 2016).…”
Section: Comparison Of Moderately-hopped Spent Yeast To Monensinmentioning
confidence: 91%
“…The composition of the bluestem hay, as determined by the Texas A&M AgriLife Extension Service Soil, Water and Forage Testing Laboratory (soiltesting.tamu.edu), was 4.8% crude protein, 39.8% acid detergent fiber, 52.5% total digestible nutrients-based acid detergent fiber, and 0.53, 0.56, and 0.23 Mcal/kg net energy for lactation, maintenance, and gain, respectively. The Chinook hops and Galena hops pellets used for both compost simulations were provided by Lupulin Exchange (Charlottesville, VA, USA) and their composition, with α-acid contents of about 12 and 13%, and β-acid contents of about 3 and 9%, respectively, have been described earlier [31]. The α-acids and β-acids from hops exhibit antimicrobial properties [23,31,32], with β-acids more specifically affecting amino acid-degrading, hyper ammonia-producing bacteria [33].…”
Section: Poultry Litter Ground Forage and Hop Extractsmentioning
confidence: 99%